Pelayanan Dinas Kependudukan dan Pencatatan Sipil terhadap Kepemilikan Kartu Tanda Penduduk, Kartu Keluarga dan Akta Kelahiran bagi Warga Masyarakat Kabupaten Timor Tengah Utara - Maria Silvana Efi; Yohanes G. Tuba Helan; Norani Asnawi (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to analyze the services of the population and civil registration offices towards ownership of identity cards, family cards and birth certificates for citizens of North Central Timor District. This research method is empirical juridical legal research, which is field research that examines the applicable legal provisions and the reality that occurs in the community. The aspects to be researched in this research are conducted through interviews, observation and documentation. The results showed that the service of DISDUKCAPIL TTU Regency was good enough, so that there was an increase in residents who wanted to take care of population documents, by looking at indicators of the five dimensions of public services, namely Tangible (Physical Evidence), Reliability, Responsiveness, Assurance, Empathy. Factors that hinder, namely: public awareness, distance, power outages resulting in disrupted networks, damage to tools/machines. Efforts of DISDUKCAPIL TTU Regency; conducting socialization related to the importance of ownership of population documents, conducting online ball pick-up activities, providing special services to people with disabilities, coordinating with parties related to public services to be able to get services from DISDUKCAPIL.